(untitled) (International Journal of Engineering and Computer Science, 2017)
A novel dual-broadband planar antenna is proposed for 2G/3G/LTE (4G) mobile base stations. The proposed antenna consists of two elements one for the upper band and another for lower band. It can also be arrayed without grating lobes. The lower band has the pair of printed dipoles with a pair of parasitic elements for bandwidth enhancement. The upper band consists of a pair of folded dipoles. Both the dipoles and the microstrip line are etched on the same substrate. The upper band elements are nested inside the lower band elements forming a compact structure. The dual-broadband antenna achieves a bandwidth of around 2 GHz. The designed antenna can be implemented in mobile base stations. The antenna gain achieved around 12 dBi which is suitable for the mobile communication base station systems.